Parent and healthcare professional experiences of critical congenital heart disease in New Zealand to advance health equity - Simone Watkins; Kim Ward; Rachel Brown; Sue Crengle; Monique WM de Laat; Teuila Percival; Lynn Sadler; Elza Cloete; Ruth Gorinski; Thomas Gentles; Frank H. Bloomfield (BMC Health Services Research, 2024)
Abstract Background Higher odds of survival have been reported in European infants compared to Indigenous Māori and Pasifika infants with critical congenital heart disease in New Zealand. We therefore aimed to understand how to mitigate this disparity by investigating the parent and healthcare professional experiences’ of critical congenital heart disease healthcare in New Zealand. Methods A prospective qualitative study utilising semi-structured interviews was conducted on a cohort of purposefully sampled parents and health professionals with experience of critical congenital heart disease healthcare in New Zealand. Parents were recruited after a fetal critical congenital heart disease diagnosis and offered two interviews at least three months apart, whilst multidisciplinary fetal and cardiosurgical health professionals were interviewed once. Interviews were recorded and transcribed verbatim before coding, categorization and qualitative analysis. Results During 2022 and 2023, 45 people participated in 57 interviews (25 parents: 19 mothers, 6 fathers; Indigenous Māori, n = 5; Pasifika, n = 6; Asian, n = 4; European, n = 10; and 20 healthcare professionals: European n = 17). The three lessons learned from participants were: (1) Minoritized groups experience disparate healthcare quality; (2) healthcare systems are under-resourced to provide equitable support for the differential needs of grieving parents; and (3) healthcare systems could engage minoritized families more optimally in shared decision-making. Conclusions According to the experiences of parents and healthcare professionals, persisting inequities in CCHD healthcare quality occur by ethnic group, with the New Zealand healthcare system privileging European families. The concepts from this study could be translated by healthcare leaders, policymakers, and professionals into evidence-based healthcare system improvements to enhance experiences for non-European families more broadly.